The Effect of the Montessori Method on the Fourth-Grade Primary Students’ Learning Outcomes in Theme VIII Region Where I Live - Gapana Sembiring, Firenta; Janson Silaban, Patri; Lumbanraja, Bogor; Sipayung, Regina; Lumban Gaol, Rumiris (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
This research aims to determine the effect of the Montessori method on the fourth-grade student learning outcomes in theme VIII in the area where I live at state elementary school 040491 Batukarang in the academic year 2022/2023. This research used quantitative methods. The research population was 25 class IV students at SD Negeri 040491 Batukarang, which consisted of 10 male and 15 female students. Sampling was taken using purposive sampling, which was 25 class IV students. The research results show that student learning outcomes using the Montessori method are in the good category with an average of 80,2 with a correlation test result of 0.937. It means that rcount (0.937) ≥ rtable (0.396), so Ha is accepted. Therefore, there is a very strong effect between the use of the Montessori method on the fourth-grade student learning outcomes in theme VIII in the area where I live at SD Negeri 040491 Batukarang. It can be seen from the T-test research results where tcount 12,918 ≥ ttable 1.708 so it can be stated that Ha is accepted. This indicates that there is a significant positive effect from the use of the Montessori method on the fourth-grade student learning outcomes in theme VIII in the area where I live at SD Negeri 040491 Batukarang in the academic year 2022/2023.